Detection of Pig DNA Contamination in Facial Creams Containing Collagen Using Conventional PCR - Fitria, Meutia Srikandi; Dewi, Juliana Permata; Mukaromah, Ana Hidayati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Semarang, 2024)
Background: Cosmetics are pharmaceutical preparations intended to support appearance or care for the body. Both local and imported facial whitening products are mostly marketed at varying prices, from cheap to expensive, making more people buy them. The supply of collagen extracted from mammals has recently been limited and is mostly obtained from the tendons and skin of cattle and pigs. The collagen content not listed on cosmetic packaging makes people worried about pork collagen being contaminated, therefore detection is needed to find out. This research aimed to detect whether there was pork contamination in facial cream products containing collagen with Cytochrome b (Cyt-b) primers using conventional PCR. Method: The research design is exploratory. The samples used were 5 facial cream samples and one positive control. Samples were subjected to DNA extraction, DNA concentration quantification, PCR, and DNA electrophoresis. Result: In the positive control, a DNA band of 149 bp specifically targeting Cytochrome b was formed, while the facial cream sample did not form a DNA band. Conclusion: The five facial creams used as samples were not contaminated with pork contamination.